2019
DOI: 10.4103/jrms.jrms_398_19
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of adapalene 0.1% with intense pulsed light versus benzoyl peroxide 5% with intense pulsed light in the treatment of acne vulgaris: A comparative study

Abstract: Background:Acne vulgaris (AV) is one of the most common skin diseases with major psychological impacts. Hence, selecting the best treatment modality is so important; there are different ways to treat AV such as topical and systemic agents, laser, and also photodynamic therapy. In this study, we tried to assess the difference between the efficacy of combination therapy with intense pulsed light (IPL) and benzoyl peroxide (BPO) in comparison with IPL and adapalene (AD) in the treatment of the mild to moderate AV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…There are many reports confirming that the IPL procedure is accompanied by pain and burning, as well as significant postoperative redness of the skin. 34,35 In our study, as it has already been emphasized, no such side effects were found.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…There are many reports confirming that the IPL procedure is accompanied by pain and burning, as well as significant postoperative redness of the skin. 34,35 In our study, as it has already been emphasized, no such side effects were found.…”
Section: Discussionsupporting
confidence: 69%
“…It also seems very important that all the abovementioned studies, including LED, IPL or LLLT, were based on counting acne lesions and assessing the final effect based on photographic documentation. 15,[31][32][33][34]36 In our study, due to sebumetric measurement, the effect of the performed procedures on the activity of sebaceous glands was also analyzed. Thus, it was proved that a series of six treatments using a low level near-infrared laser, apart from reducing all types of acne lesions, finally resulted in a statistically significant reduction in the amount of sebum secreted, which confirms the conclusions drawn earlier based on the research conducted by Jung et al in vitro study.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] Fractional carbon dioxide (CO 2 ) laser is among the early light-based modalities with acceptable results in various dermatological conditions including acne scars, with fewer post-treatment complications than CO 2 laser. [ 8 12 ] Fractional CO 2 has been used as a monotherapy and has shown to result in mild to significant improvements in almost 80% of acne scars with minimal side effects. [ 8 30 31 ] According to the available data, the use of CO 2 should be based on the characteristics of the scar, individualized plans, and the patient-side issues.…”
Section: Discussionmentioning
confidence: 99%
“…This originates from the aberrant production and deposition of collagen around inflamed follicles, resulting in visibly depressed scars. [ 8 ] Acne scars can be classified into three groups: atrophic scar, hypertrophic scar, and keloid. Atrophic acne scar can be categorized into three sub-types: ice-pick scar, rolling scar, and boxcar scar according to their width, depth, and three-dimensional architectures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation